Design of the Mathsolve Learning Media with a Problem-Solving Approach by Schoenfeld on Sequences and Series Material - Purnomo, Eko Andy; Aziz, Abdul; Hartanti, Intan Pramuditya (Universitas Teknokrat Indonesia, 2025)
Sequences and series are mathematical topics closely related to everyday life. however, many students face difficulties in comprehensively understanding them. Based on the needs analysis, it was found that students require technology based learning media that can support their learning process more effectively. This study aims to develop the design of a website based learning media called mathsolve, which is structured using schoenfeld problem solving steps. The research method employed is Research and Development (RnD) with the 4D model (Define, Design, Develop, Disseminate), limited to the design stage to focus on developing a well constructed and conceptually tested learning media design before proceeding to further development. The design process involved in depth needs analysis, intensive discussions among the research team, and iterative revisions to ensure the quality of the design. The result of this study is the design of the mathsolve learning media, which includes features such as interactive videos, practice problems, and story problems guided by Schoenfeld problem solving framework. The mathsolve website design can be accessed at www.mathsolve.blog. This design is expected to provide an innovative solution to facilitate students independent learning of sequences and series material and serve as a reference for further research focused on the development and implementation of technology-based learning media on a broader scale.